2018
DOI: 10.12998/wjcc.v6.i3.27
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical efficacy of two different types of post systems which were restored with composite restorations

Abstract: AIMTo compare the efficacy of resin composite restorations, retained with either polyethylene or zirconia-rich glass fiber posts.METHODSSixty-two single rooted maxillary and mandibular central incisor teeth in forty-four patients (15 males and 29 females; age range 15-32 years) were restored either with an ultrahigh molecular weight polyethylene (UHMWP) fiber post (Bondable Reinforcement Ribbon, DENSE, Ribbond, Seattle, WA, United States) or a zircon-rich glass fiber post (Snowpost, Lot H 040; Carbotech, Gange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…15 Aesthetic posts (fiber or ceramic-based) are given preference compared with the metallic posts because of their ability to transmit light, superior biocompatibility, and lack of the ability to alter the restoration's color. 15,16 The yttria-stabilized tetragonal zirconia polycrystalline (Y-TZP) are zirconium-based aesthetic dental posts with acceptable biocompatibility. 17 The zirconia posts bear a good resemblance to the tooth color, serve as an alternative to metal restorations, and possess long-term chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…15 Aesthetic posts (fiber or ceramic-based) are given preference compared with the metallic posts because of their ability to transmit light, superior biocompatibility, and lack of the ability to alter the restoration's color. 15,16 The yttria-stabilized tetragonal zirconia polycrystalline (Y-TZP) are zirconium-based aesthetic dental posts with acceptable biocompatibility. 17 The zirconia posts bear a good resemblance to the tooth color, serve as an alternative to metal restorations, and possess long-term chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…(14) Therefore, to create a monoblock effect that increases the tooth's resistance to fracture, the use of post material with an elastic modulus closer to that of the tooth dentine and the post's ability to bond to dentine and resin cement are both essential. (17,20) All materials utilized and investigated in the current study were used following the manufacturer's instructions. (18) Because eugenol-containing sealers could affect resin cement's polymerization and interfere with its ability to adhere, ADSEAL resin sealer was employed.…”
Section: Discussionmentioning
confidence: 99%
“…It results, after adhesive cementation with resin cement to the radicular dentin, in the formation of a monoblock effect which increases the longterm success of these restorations along with improvement in esthetics and function. (8) On the other hand, better stress distribution is provided by a custom-made post and core system than by a prefabricated glass fiber post, as the latter has multiple interfaces with different modulus of elasticity. (9,10) Therefore, a custommade post and core composed of milled polymer polyetheretherketone (PEEK) resin had good dimensional stability, biocompatibility, was simple to polish, and was machinable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, differing from the findings obtained in this research, Scotti et al (2015) affirm that endodontically treated posterior teeth with GFP showed an increase in fracture strength. Additionally, Ayna et al (2018) report that GFP may be used clinically to aid the retention of CR restorations, increasing the resistance of the tooth/restoration set. Corrêa et al (2018) state that teeth with GFP are more prone to repairable fractures when compared to teeth with cast metal core.…”
Section: Discussionmentioning
confidence: 99%